2020
DOI: 10.1111/jcmm.15494
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1‐mediated deacetylation of LSD1 regulates vascular calcification by promoting autophagy in chronic renal failure

Abstract: Chronic renal failure (CRF) is commonly associated with various adverse consequences including pathological vascular calcification (VC), which represents a significant clinical concern. Existing literature has suggested the involvement of histone deacetylases (HDACs) in the progression of CRF‐induced VC. However, the underlying molecular mechanisms associated with HDACs remain largely unknown. Therefore, we established the adenine‐induced CRF rat model and in vitro VC models based on vascular smooth muscle cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
1
12
1
Order By: Relevance
“…Autophagic flux was upregulated in VCN in both a chronic in vivo renal failure rat model, as well as in an in vitro Pi-induced VSMC calcification assay [ 51 ]. This observation was also confirmed in other studies, where autophagy was upregulated in in vitro and in vivo models of VCN [ 52 , 53 ]. Conversely, there is also evidence that mTOR (an inhibitor of autophagy) is upregulated in VSMC calcification [ 54 ].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Autophagic flux was upregulated in VCN in both a chronic in vivo renal failure rat model, as well as in an in vitro Pi-induced VSMC calcification assay [ 51 ]. This observation was also confirmed in other studies, where autophagy was upregulated in in vitro and in vivo models of VCN [ 52 , 53 ]. Conversely, there is also evidence that mTOR (an inhibitor of autophagy) is upregulated in VSMC calcification [ 54 ].…”
Section: Resultssupporting
confidence: 89%
“…Dai et al (2013a) showed that inhibiting autophagy with 3-MA or Atg5 knockdown enhances VCN in vitro. Other studies confirmed that 3-MA aggravates VSMC calcification [52,53,72]. Furthermore, multiple studies added 3-MA, in combination with an autophagy, inducing pharmacological intervention, thereby showing that 3-MA abolishes the beneficial effects of autophagy induction on VCN [59,61,64,66,67].…”
Section: Inhibiting Autophagy In Vascular Calcificationmentioning
confidence: 85%
See 2 more Smart Citations
“…DD406/7 are identified as key residues for GTPase-activating protein (GAP) activity toward recombination activating genes (RAGs) (GATOR) 2 binding so that Sestrin2 can inhibit mTORC1 association with lysosome for its activation Ho et al, 2016). LSD1, upon deacetylation by histone deacetylase 1 (HDAC1), reduced the methylations of H3K4me2 in the promoter region of Sesn2, thereby suppressed the gene expression of Sesn2 in chronic renal failure (CRF) (Zhou et al, 2020). Jumonji domain-containing protein D3 (JMJD3), a histone demethylase, inhibited the transcription of Sesn2 by reducing the methylations of H3K27me3 in the promoter region of Sesn2 in cardiomyopathy (Wang P. et al, 2020).…”
Section: Introduction Of Sestrinsmentioning
confidence: 99%